Macroeconomic Perspectives and Consequences of Introducing Euro in Poland - Dybizbańska, Agnieszka (Makroekonomiczne perspektywy i konsekwencje wprowadzenia euro w Polsce, 2010)
The objective of this article is to indentify costs and benefits of introducing common currency in Poland paying special attention to macroeconomic consequences. The main themes are: present level of nominal convergence, balance of costs and benefits which are significant from the Polish economy point of view as well as risks and chances involved in the adoption of euro. The article sums up the perspectives and possible consequences of adopting single currency which might be expected and taken into consideration before joining the Exchange Rate Mechanism II.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 136, s. 31-41
Keywords: convergence criteria; ERM II; euro; exchange rate; monetary union